2021
DOI: 10.1039/d1ra03071j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, oligomerization and catalytic studies of a redox-active Ni4-cubane: a detailed mechanistic investigation

Abstract: A robust tetrameric nickel complex [Ni4((Oal−)2L-Me)4(s)4] (s = solvent) with cubane-like Ni4O4 core topology identified as the efficient catalyst for the diastereoselective cyclopropanation of aromatic heterocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Complex 1 displays oligomerisation with n = 1 to 8 in non-coordinating polar aprotic solvents. 38 The electrospray ionisation mass spectrometry (ESI-MS) measurements of 1 showed that the predominating oligomers are n = 4, 5, and 6 in acetonitrile/THF. 38 The oligomers of 1 are in equilibrium with each other in the solution.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Complex 1 displays oligomerisation with n = 1 to 8 in non-coordinating polar aprotic solvents. 38 The electrospray ionisation mass spectrometry (ESI-MS) measurements of 1 showed that the predominating oligomers are n = 4, 5, and 6 in acetonitrile/THF. 38 The oligomers of 1 are in equilibrium with each other in the solution.…”
Section: Resultsmentioning
confidence: 99%
“…38 The electrospray ionisation mass spectrometry (ESI-MS) measurements of 1 showed that the predominating oligomers are n = 4, 5, and 6 in acetonitrile/THF. 38 The oligomers of 1 are in equilibrium with each other in the solution. However, 1 is only isolated as a tetramer in the solid state.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations